A multi-method quality improvement approach to systematically improve and promote the quality of national health and social care information. Issue 1 (January 2022) - McGrath, Niamh; Foley, Barbara; Hurley, Caroline; Ryan, Maria; Flynn, Rachel
Safe and reliable healthcare depends on access to health information that is accurate, valid, reliable, timely, relevant, legible and complete. National data collections are repositories of health and social care data and play a crucial role in healthcare planning and clinical decision-making. We describe the development of an evidence-informed multi-method quality improvement program aimed to improve the quality of health and social care data in Ireland. Specific components involved: development of guidance to support implementation of health information standards; review program to assess compliance with standards; and educating health information stakeholders about health data and information quality. Observations from implementation of the program indicate enhanced health information stakeholder awareness of, and increased adoption of information management standards. The methodology used in the review program has proved to be a robust approach to identify areas of good practice and opportunities for improvement in information management practices. There has been positive adoption of the program among organisations reviewed and acceptance of the proposed recommendations. Early indications are that this multi-method approach will drive improvements in information management practices, leading to an improvement in health and social care data quality in Ireland. Aspects of this approach may be adapted to meet the needs of other countries.